Is there evidence for clinical differences related to the new classification of temporal lobe cortical dysplasia?. Issue 5 (29th March 2013) - Fauser, Susanne; Essang, Charles; Altenmüller, Dirk Matthias; Staack, Anke; Steinhoff, Bernhard J.; Strobl, Karl; Bast, Thomas; Schubert‐Bast, Susanne; Doostkam, Soroush; Zentner, Josef; Schulze‐Bonhage, Andreas
Summary Purpose The new International League Against Epilepsy (ILAE) classification for focal cortical dysplasia (FCD) differentiates between patients with isolated FCD (type 1) and FCD with an associated hippocampal sclerosis (HS) (type 3a). In contrast to the former FCD classification by Palmini, which considered only histologic features, the novel ILAE classification also relies on magnetic resonance imaging (MRI) findings and presumed pathogenesis. We investigated in a cohort of 100 patients with exclusively temporal FCD if the new subdivision of FCD is reflected in clinical characteristics. Methods Thirty‐one patients with FCD type 1 and 50 patients with FCD type 3a in the temporal lobe were included. In all patients MRI and histology of the FCD were available. Both patient groups were compared to 19 patients with temporal FCD type 2 with clearly different histologic appearance. Key Findings Patients with FCD type 1 and type 3a presented with similar clinical features in many respects. In univariate analyses, no statistically significant differences were found as to age at epilepsy onset (p = 0.07) and epilepsy surgery (p = 0.14), a normal appearing neocortical temporal lobe (p = 0.08) or diagnosis of FCD by visual inspection of MRI (p = 0.08), preoperative seizure frequency (p = 0.06), and the predominance of an epigastric aura (p = 0.08). The postoperative outcome was nearly identical 1 year (p = 0.8) and 2 (p = 0.8), 3 (p = 0.8), 5 (p = 0.7), and 8 (p = 1.0) years postoperatively. Only febrile seizures (p = 0.025) and an aura (p = 0.03) were significantly more frequently reported in patients with FCD type 3a. Similar results were obtained from a multivariate logistic regression analysis. Patients with FCD type 2 were more different: Compared to FCD type 3a, age at epilepsy surgery was significantly lower (p = 0.004) and auras (p = 0.005) were significantly less frequently reported. Epigastric auras (p = 0.04) and febrile seizures (p = 0.025) occurred significantly less frequently in patients with FCD type 2 without HS compared to FCD type 3a. The diagnosis of an FCD was significantly more frequently made (p = 0.03) by visual inspection of the MRI compared to FCD type 1. Significance Clinical features did not allow to clear separation of temporal FCD types 1 and 3a. Statistically significant differences were seen in a history of febrile seizures and the occurrence of auras more common in FCD type 3a. However, FCD type 2 in the same localization but with different histology presented with further differences such as more frequent FCD diagnosis by visual inspection of MRI, earlier operation, and less frequent epigastric auras.